Lacunary Statistical Limit Points in Random 2-Normed Spaces. (1st July 2013) - Güncan, A.; Yamancı, U.; Gürdal, M.
Abstract : We introduce the notion θ -cluster points, investigate the relation between θ -cluster points and limit points of sequences in the topology induced by random 2-normed spaces, and prove some important results.